Vesicoureteral Reflux in the Child with Lazy Bladder Syndrome: The Infrequent Voider - Marco Grasso; Fabrizio Torelli; Salvatore Blanco; Flavio Fortuna; Marco Baruffi (Advances in Urology)
The Infrequent Voider Syndrome or Lazy Bladder Syndrome in children is characterized by a large capacity bladder, frequently associated with a significant volume of residual urine. Usually these patients arrive at medical examination with a history of recurrent urinary infections but without anomalies in the upper urinary tract. We report about a young girl affected by one-sided 2∘ degree vesico-ureteral reflux due to Lazy Bladder Syndrome that had never been diagnosed before. This patient has been submitted to a prompt bladder training and seems presently to have at last gained a physiological micturition after 9 months of follow-up, without actual evidence of vesicoureteral reflux. Therefore we must stress that it is prominently important considering about infrequent micturition in a paediatric case history or a large capacity bladder, possible presence of bladder dysfunction and vesicoureteral reflux too.